PERAN CUSTOMER RELATIONSHIP MANAGEMENT DALAM MENINGKATKAN EFEKTIVITAS PELAYANAN PURNA JUAL PADA CV. CAHAYA BONANZA ABADI - Salwa Meindika Az-Zahra; Fani Khoirotunnisa (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2026)
This study aims to analyze the effectiveness of implementing digital chat and telephone-based Customer Relationship Management (CRM) in improving after-sales service at CV. Cahaya Bonanza Abadi Motor, specifically related to customer relations, operational compliance, and resale opportunities. This study uses a qualitative method with a descriptive approach, where data is collected through structured interviews and document observations to informants selected using purposive sampling, including dealer CRM staff, workshop CRM staff, customer service, and sales staff. The results show that the implementation of CRM is in accordance with the IDIC stages of identify, differentiate, interact, and customize, which is seen through the process of identifying customer data, segmenting based on service needs and document status, routine interactions through digital messages, and service adjustments based on customer history. CRM has been proven to increase customer loyalty, strengthen the frequency of service visits, and help the company meet MPM procedure standards related to STNK/BPKB management and KPB targets. In addition, CRM contributes to increasing upselling opportunities and new unit sales through the utilization of customer segmentation based on the age of the last vehicle purchased. These findings indicate that CRM not only functions as a means of communication but also as a managerial instrument that can improve operational efficiency, after-sales service quality, and company competitiveness.